Adsorption and Release Mechanism of Polypeptide on Magnetic Mesoporous Carbons - Chen, Ren-Hong; Zhong, Guo-Ying; Wang, Xiu-Fang (Asian Journal of Chemistry, 2013)
Magnetic Fe-containing mesoporous carbons with high surface areas and pore volume were synthesized through a simple soft-template route, wherein phenolic resin was used as a carbon precursor, triblock copolymer F127 as a template agent, tetraethyl orthosilicate as a silica precursor and hydrated iron nitrite as an iron source. Dynorphin A (1-13) was selected as polypeptide drug model. The adsorption and release behaviour of dynorphin A (1-13) on magnetic mesoporous carbons were investigated. The adsorption capacity of dynorphin A (1-13) on magnetic mesoporous carbons was mainly the function of the specific surface area, pore volume of the material and the pH value of solution. The adsorption amount of dynorphin A(1-13) increased with the increase of the specific surface area and pore volume of the materials and pH value of solution, due to the electrostatic interaction between dynorphin A(1-13) molecules and carbon, as well as the electrostatic interaction between dynorphin A(1-13) molecules and dynorphin A(1-13) molecules. The two-step release process involved a first fast release and then a slower release. The release behaviour of dynorphin A (1-13) was well correlated with time using a simple exponential equation. The pore size was a crucial factor for the release rate of dynorphin A (1-13), which increased with the increase of pore size.